2015
DOI: 10.1039/c4ra15901b
|View full text |Cite
|
Sign up to set email alerts
|

Iron metal induced deoxygenation of graphite oxide nanosheets-insights on the capacitive properties of binder-free electrodes

Abstract: The capacitive behaviour of iron reduced graphite oxide in alkaline media is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The extent of reduction of GO can be clearly observed from Figure b from the randomly corrugated, disordered and crumpled or folded sheets with minimal aggregation. This type of corrugated structure could reduce sheet restacking to a greater extent compared to that of the rGOs prepared via other wet chemical methods that generally tend to aggregate, thus accruing its potential for electrical applications. The HR‐TEM image of rGO is shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of reduction of GO can be clearly observed from Figure b from the randomly corrugated, disordered and crumpled or folded sheets with minimal aggregation. This type of corrugated structure could reduce sheet restacking to a greater extent compared to that of the rGOs prepared via other wet chemical methods that generally tend to aggregate, thus accruing its potential for electrical applications. The HR‐TEM image of rGO is shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…Previously iron metal powder was employed as an effective reductant to reduce graphite oxide. The resulting rGO was found to have good aspect ratio and showed pronounced electrochemical activity as an electrode material for supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…GO was deoxygenated using metal salt, tin (II) chloride, [26] and a metal powder, iron (Fe) [27] to yield Sn-RGO and Fe-RGO, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental results showed that the RGO anode can deliver a specific discharge capacity of 272 mA h g -1 at 50 mA g -1 (second cycle) with a good cycling stability and a superior rate capability. For comparison, we also prepared RGO using iron (Fe) metal powder as a reducing agent [27]. Both experimental and computer-simulation data indicate that the energy storage mechanism is surface-driven, where reactions between Na + and the defects on the surface of RGOs advantageously influence the interfacial activity between electrode and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Only one prominent C1s peak was observed at 284.8 eV suggesting the sp 2 graphitic nature of the sample. domains during reduction and increased graphitization [14,16].…”
Section: Electrode Preparation and Electrochemical Measurementsmentioning
confidence: 99%